2011
DOI: 10.1177/2041301710394921
|View full text |Cite
|
Sign up to set email alerts
|

Field investigations into the adhesion recovery in leaf-contaminated wheel–rail contacts with locomotive sanders

Abstract: Locomotives of railways worldwide have been using sand since 1838 to improve the wheel-rail adhesion during traction and braking operations. In more recent years, sanders have also been fitted to electrical and diesel multiple units in some railways to fight (often in combination with traction control or wheel slide protection systems) the low-adhesion conditions, especially encountered in autumn due to leaf contamination. In spite of the worldwide broad use of sand, different standards on sanding practice app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 8 publications
2
45
0
Order By: Relevance
“…Leaf fall can also cause a lot disturbance to traffic on the network [45]. Research into leaf contamination and low adhesion has been carried out using various methods including actual trains [67], pin-on-disc [58,68], twin-disc [69,70] and ball-on-disc [71] test rigs. A comparison of these tests was discussed in [72], and is shown in Table 4.…”
Section: Wheel-rail Adhesion Under Contaminated Conditionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Leaf fall can also cause a lot disturbance to traffic on the network [45]. Research into leaf contamination and low adhesion has been carried out using various methods including actual trains [67], pin-on-disc [58,68], twin-disc [69,70] and ball-on-disc [71] test rigs. A comparison of these tests was discussed in [72], and is shown in Table 4.…”
Section: Wheel-rail Adhesion Under Contaminated Conditionsmentioning
confidence: 99%
“…It was pointed out that with increased thickness of the oxide layer on the railhead surface the friction coefficient reduces [72] although no definitive relationship was found between leaf contamination thickness and the friction levels [64]. [68] GallardoHernandez and Lewis [70] Li et al [69] Cann [71] Arias-Cuevas and Li [67] Test apparatus Pin-on-disc …”
Section: Wheel-rail Adhesion Under Contaminated Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, low adhesion problems have been present in many railway networks in recent decades, especially those related to leaf contamination in autumn [1][2][3][4]. Recent field investigations have demonstrated that leaf layers in dry conditions can lead to low adhesion incidents as well as in humid conditions [5]. Since the beginning of railways, sanding from the locomotive has been a common practice to enhance the wheel-rail adhesion [6].…”
Section: Introductionmentioning
confidence: 99%